Whitesmith Consulting: Untangling Service-for-Equity Arrangements - Henderson, James; Leleux, Benoit; White, Ian (Senate Hall, 2003)
Many service organizations over the last few years have attempted to migrate, sometimes reluctantly and experimentally, from their traditional modus operandi (fee-for-service) to various forms of equity-for-service arrangements. The conversion to an equity-incentivized model could be both defensive (to retain human capital and/or slow down defections to startup companies) and offensive (to generate new business from cash-poor, prospect-rich companies and leverage the firm's core competencies). This case is designed for students to address the strategic, financial, and organizational issues of such equity-enabled arrangements, and to gain a better understanding of the underlying risks and benefits of such innovative service models. It also offers managerial guidance for effective implementation of equity-for-service arrangements.
Keywords: equity-enabled contracts|equity-for-service arrangements|strategy consulting|entrepreneurial realignment of interest|conflicts of interest|professional ethics